2016
DOI: 10.13065/jksdh.2016.16.03.491
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors for perceived oral health for the improvement of quality of life in Korean elderly

Abstract: Objectives:The purpose of the study was to investigate the influencing factors of the perceived oral health for improvement of quality of life in Korean elderly. Methods: The subjects were 1,289 elderly over 65 years old from the sixth National Health and Nutrition Examination Survey 2013. The dependent variable was subjective oral health status. The independent variable was sociodemographic characteristics. Results: The perceived oral health of the unemployed elderly and those having chewing problems were 1.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…Yang and Seo [15] reported a significant difference in oral health behavior in the elderly according to income and educational level. This current study was inconsistent with the results of Oh and Kim [19], but was similar to Yang and Seo [15]. Self-rated oral health was more likely to be better in the oldest individuals in the study, educational level, and in males than in females, with a monthly income of more than 6,000,000 won compared with elderly people with a monthly income of 500,000 won.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Yang and Seo [15] reported a significant difference in oral health behavior in the elderly according to income and educational level. This current study was inconsistent with the results of Oh and Kim [19], but was similar to Yang and Seo [15]. Self-rated oral health was more likely to be better in the oldest individuals in the study, educational level, and in males than in females, with a monthly income of more than 6,000,000 won compared with elderly people with a monthly income of 500,000 won.…”
Section: Discussioncontrasting
confidence: 99%
“…General and socio-economic characteristics such as age, gender, educational level, monthly income, and living status were factors affecting self-rated oral health. In the study of Oh and Kim [ 19 ], the variables that differed according to the self-rated health of the elderly were occupation, and medical care, and the influencing factors were 1.65 times stronger compared with those without an occupation. Yang and Seo [ 15 ] reported a significant difference in oral health behavior in the elderly according to income and educational level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after controlling for demographic, economic, and health-related factors, it was found that oral health had a large effect on the nutritional status of the elderly [ 7 ]. A small number of remaining teeth or a large number of missing teeth causes disturbances in food intake, limiting the range of food choices and reducing the quantity and quality of meals of the elderly, in turn affecting their health maintenance [ 29 ]. It has been reported that oral diseases and mastication-related problems increase with age and decrease the quality of life [ 30 ].…”
Section: Discussionmentioning
confidence: 99%